Fabrication of the membranes on a silicon base for the sensors with the ultrasonic waves Lamba-type generated by using the interdigital transducers - GOŁĘBIOWSKI, J. (Archives of Acoustics, 2000)
The construction of the microsensor with the ultrasonic wave of Lamba-type as well as the conditions of the wave propagation are presented. The possibilities of the fabrication of multi-layer membranes on a silicon base using the microelectronics technologies are presented and discussed. The analysis of the usefulness of the processes mentioned for the production of thin membrane sensors was carried out taking into consideration intrinsic stresses. A summary of the experimental results is given and the most useful parameters of the membrane ultrasonic sensors are pointed out.